Hoarding of Personal Protection Tools during the Covid-19 Pandemic: Criminal Law Study on Consumer Protection - Wandi Subroto (Budapest International Research and Critics University, 2022)
During the pandemic, some unscrupulous perpetrators hoard Personal Protective Equipment (PPE), which then causes a shortage and an increase in the price of PPE. This is a problem that is quite worrying for consumer protection. This study will examine how criminal law in consumer protection looks at the issues regarding the hoarding of PPE by these elements. The research will be carried out using a normative juridical method. The approach used is a statute approach and a conceptual approach by looking at the law, research results, and previous studies related to this research. The study results found that criminal law plays an essential role in consumer protection. Then this criminal law can be used to take action against the perpetrators of hoarding PPE based on the Trade Law and the Business Competition Law.